On Stock Market Returns and Monetary Policy - Thorbecke, Willem (Journal of Finance, 1997)
Financial economists have long debated whether monetary policy is neutral. This article addresses this question by examining how stock return data respond to monetary policy shocks. Monetary policy is measured by innovations in the federal funds rate and nonborrowed reserves, by narrative indicators, and by an event study of Federal Reserve policy changes. In every case the evidence indicates that expansionary policy increases ex-post stock returns. Results from estimating a multi-factor model also indicate that exposure to monetary policy increases an asset's ex-ante return.